Evaluation of the methodological quality of articles on autologous breast reconstruction. Issue 9 (September 2018) - Schülein, Stefanie; Taylor, Katherine J.; Braun, Bettina; Heyl, Volker; Zoche, Hermann; Peek, Alberto; Solbach, Christine; Schott, Sarah; Blettner, Maria; Klug, Stefanie J.
Abstract: Background: Breast cancer remains the most common cancer among women worldwide. Autologous breast reconstruction may contribute toward restoring body image and improving quality of life after mastectomy. This systematic literature review describes differences in the quality and type of studies investigating autologous breast reconstruction techniques over time. Methods: MEDLINE was searched for articles related to the surgical techniques, namely, TRAM, LADO, DIEP, and SGAP/IGAP, for the periods 1970 to 2007 and 2008 to 2010. The quality and type of studies were compared across the two time periods. Full-texts were evaluated according to prespecified quality criteria. Results: The MEDLINE searches yielded 1, 057 articles for review; of them, 517 articles were excluded, and 314 had a completed quality criteria checklist and hence were included; of these 314 articles, 206 articles investigated TRAM flaps, 85 investigated LADO flaps, 74 investigated DIEP flaps, and 6 investigated SGAP/IGAP flaps. A total of 218 articles were published between 1970 and 2007 compared to 96 articles published between 2008 and 2010. The comparison of quality scores between the two time periods showed a shift toward higher scores in the period 2008 to 2010. The DIEP technique was investigated more frequently between 2008 and 2010 than between 1970 and 2007, whereas the percentage of articles focusing on the TRAM flap decreased. The percentage of articles investigating the LADO and SGAP/IGAP techniques remained constant across the time periods. Conclusions: Results relating to the methodological quality of articles on breast reconstruction with autologous tissue show that the quality of publications has improved with time, whereas research interests concerning the type of surgical technique investigated have changed in focus.